The Impact of Strategic Thinking Skills on Enhancing Strategic Response Processes: Analytical Research on the Opinions of a Sample of Medical and Nursing Staff in Private Hospitals in Karbala - Hurajah ALHasnawi, Hussein; Hussein Jawad Al-Mousawi, Maryam (Iraqi Journal for Administrative Sciences, 2025)
The present research aims to determine the impact relationships and the relationship between strategic thinking skills and strategic response processes at the level of a sample of medical and nursing staff working in private hospitals in the holy province of Karbala, where the measurement of strategic thinking skills through three dimensions are (meditation, organizational thinking and reformulation) Strategic response processes were measured in four dimensions (resource liquidity, business process maturity, business response to the environment and proactive business to the environment), and the research relied on a descriptive and analytical approach to the collection and analysis of research information. The questionnaire was used to collect data and information from a sample of (218) of the medical and nursing staff of the hospital staff. The natural distribution test, empirical factor analysis, descriptive statistics, simple correlation analysis (Pearson), structural equation modeling (SEM) were used. And Path Analysis through statistical programs (Microsoft Excel 2010, SPSS V.25, Amos V.23). The research reached a number of conclusions, the most important of which was the presence of a direct significant significance of strategic thinking skills in the strategic response processes, as well as a set of recommendations, the most important of which is the need to fully orient towards the development of strategic thinking skills of its members doctors and nurses in order to ensure the improvement of their ability To achieve strategic response to various environmental conditions.